Hybrid presence: Integrating interprofessional interactions with digital consultations - Simonsen Line Maria (Nordicom Review)
Healthcare practitioners struggle to adapt to the changes that new digital media entail for social interactions, but what does the struggle look like, and how is it embedded in these professionals’ everyday experiences? I investigate these questions in this study of how digitalisation conditions social interactions in the context of the Danish medical setting by drawing on ethnographic work. Moreover, via a video-recorded case study, this article shows how two practitioners organise social actions by exploiting features of a digital communication system in a situation where they manage a practical problem. I propose the concept of hybrid presence related to the scientific fields of dialogism and distributed cognition as an explanation of how the participants are capable of immersing themselves with both the digital technology and the social interaction. Hybrid presence thus proves useful in the discussion of how practitioners may struggle with technology.